Guanidinyl-Functionalized Aromatic Compounds (GFAs): charge and spin density studies as starting points for the development of a new class of redox-active ligands - Himmel, Hans-Jörg (Zeitschrift für anorganische und allgemeine Chemie, 2013)
This research report is devoted to guanidinyl-functionalized aromatic compounds (GFAs), which represent a new class of strong electron donors and redox-active ligands. Charge and spin density studies provided the basis for the development of a rich coordination chemistry, which includes molecular complexes as well as 1D coordination polymers.